2019
DOI: 10.21061/jvs.v4i1.82
|View full text |Cite
|
Sign up to set email alerts
|

Supporting Military Veterans in Australian Higher Education

Abstract: Veterans often face difficulties during the transition from military to civilian life, with relatively high unemployment rates and mental health risks. Higher education represents an important pathway to navigate this transition successfully. Research from the United States shows that veterans bring unique strengths to the classroom, but also face specific challenges and barriers in accessing higher education. In Australia, military veterans have been largely invisible in the higher education sector. There is … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
9
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 10 publications
(9 citation statements)
references
References 10 publications
(16 reference statements)
0
9
0
Order By: Relevance
“…A related consideration is the issue of self-identification as a veteran. Research shows that veterans can be reluctant to disclose their veteran status due to fear of being stigmatised and stereotyped (Andrewartha & Harvey, 2019;Elliott et al, 2011). We found that one university prefers to ask if a person is a current or former member of the ADF (rather than a veteran).…”
Section: Discussionmentioning
confidence: 80%
See 3 more Smart Citations
“…A related consideration is the issue of self-identification as a veteran. Research shows that veterans can be reluctant to disclose their veteran status due to fear of being stigmatised and stereotyped (Andrewartha & Harvey, 2019;Elliott et al, 2011). We found that one university prefers to ask if a person is a current or former member of the ADF (rather than a veteran).…”
Section: Discussionmentioning
confidence: 80%
“…A common consideration in the research is that student veterans can be hesitant to disclose their veteran status. This reluctance can be partly attributed to a lack of clear benefits of disclosure, but also due to mistrust and misalignment with political culture on campus, and fear of being stigmatised, treated "differently," and falling subject to stereotyping (Andrewartha & Harvey, 2019;Elliott et al, 2011).…”
Section: Contextmentioning
confidence: 99%
See 2 more Smart Citations
“…By utilizing NVivo's word frequency query search, three topics emanate from the theme of student veterans as observed in JVS articles. They are student veteran transition experiences from military to civilian and becoming student veterans (Andrewartha & Harvey, 2019;Bodrog et al, 2018;Boettcher et al, 2017;Jenner, 2017;McMenamin, 2016;Mendez et al, 2018;Petri et al, 2016;Phillips, 2016;Pollak et al, 2019;Young, 2017), conditions surrounding student veteran academic success (Bagby et al, 2019;Blackwell-Starnes, 2018;Cipher et al, 2018;Flatt & Rhodes, 2019;Garrity, 2017;Hembrough, 2017;Hembrough et al, 2018;Spencer, 2016), and issues surrounding accommodations needed by student veterans (Flink, 2017;Kranke et al, 2017;Morris et al, 2019;Wild & Mahapatra, 2018).…”
Section: Themes From Jvs Articlesmentioning
confidence: 99%